2020
DOI: 10.3390/ijms21228857
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Pyrus betulaefolia Seedling Root Responses to Short-Term Potassium Deficiency

Abstract: Potassium (K) plays a crucial role in multiple physiological and developmental processes in plants. Its deficiency is a common abiotic stress that inhibits plant growth and reduces crop productivity. A better understanding of the mechanisms involved in plant responses to low K could help to improve the efficiency of K use in plants. However, such responses remain poorly characterized in fruit tree species such as pears (Pyrus sp). We analyzed the physiological and transcriptome responses of a commonly used pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…N affected crop growth externally by reducing leaf area and green leaf lifespan, and internally by inhibiting the synthesis of chlorophyll and protein to reduce photosynthetic products (Dos Santos et al, 2020;Mu and Chen, 2021). K + participated in protein synthesis, photosynthesis, enzyme activation, regulation of osmosis, and ion homeostasis (Li et al, 2021c), and the research of Yang, H. et al showed that under low K + condition, the K + concentration of old leaves decreased, but the concentration of new leaves changes little because of the highly mobile potassium in the crop (Yang et al, 2020). In addition, phloem transportation and biomass partitioning also depended on the regulation of K + (Li et al, 2021d).…”
Section: Experiments Designmentioning
confidence: 99%
“…N affected crop growth externally by reducing leaf area and green leaf lifespan, and internally by inhibiting the synthesis of chlorophyll and protein to reduce photosynthetic products (Dos Santos et al, 2020;Mu and Chen, 2021). K + participated in protein synthesis, photosynthesis, enzyme activation, regulation of osmosis, and ion homeostasis (Li et al, 2021c), and the research of Yang, H. et al showed that under low K + condition, the K + concentration of old leaves decreased, but the concentration of new leaves changes little because of the highly mobile potassium in the crop (Yang et al, 2020). In addition, phloem transportation and biomass partitioning also depended on the regulation of K + (Li et al, 2021d).…”
Section: Experiments Designmentioning
confidence: 99%
“…Also, only three GhHAK5 genes and one GhKUP3 gene were induced by low K + in the roots of both grafts in this study ( Figure 6 a). The transcripts of members of the KUP/HAK/KT family usually increased under K + deficiency [ 34 , 36 , 37 ]. Moreover, genotypic differences in K + efficiency were associated with the number and amplitude of up-regulated K + transporter genes in cotton [ 41 ] and wheat [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Nitrate transporter 1/peptide transporter ( NRT1/PTR ) genes regulated by external potassium has been reported for Arabidopsis [ 31 ], rice [ 34 ], wheat [ 67 ], banana [ 47 ], and pear [ 37 ]. Consistently, we identified several up-regulated GhNRT2.1s in the roots of SCRC22/CCRI41 ( Figure 6 a, b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations